2009 International Symposium on Autonomous Decentralized Systems 2009
DOI: 10.1109/isads.2009.5207344
|View full text |Cite
|
Sign up to set email alerts
|

A cross-layered communication protocol for load balancing in large scale multi-sink wireless sensor networks

Abstract: One of the fundamental operations in sensor networks is convergecast which refers to the communication pattern in which data is collected from a set of sensor nodes and forwarded to a common end-point gateway, namely sink node, in the network. In case of multiple sinks within the network, the total load of the network has to be balanced among these sinks to minimize the problem of packet loss in the convergecast process in wireless sensor networks (WSNs) due to congestion and collisions near the sinks. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…In this respect, Erman et al [14] suggested a network load balancing protocol based on cross-layer partitioning that combines the load balancing and clustering techniques in the whole network, thereby enabling the multisink network to effectively transmit data by constructing the best routing tree based on the local metric. A routing algorithm to achieve load balance between multisinks was further introduced by [15], where each data packet randomly selects only one sink as its target node.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, Erman et al [14] suggested a network load balancing protocol based on cross-layer partitioning that combines the load balancing and clustering techniques in the whole network, thereby enabling the multisink network to effectively transmit data by constructing the best routing tree based on the local metric. A routing algorithm to achieve load balance between multisinks was further introduced by [15], where each data packet randomly selects only one sink as its target node.…”
Section: Related Studiesmentioning
confidence: 99%
“…However, the sensor nodes are usually deployed in a place where it is very difficult to conduct manual maintenance within the coalmine tunnel. Some studies [14,15,16,17,18,19,20,21,22] have proposed methods relating to load balance and effectiveness of energy consumption with the aim of avoiding packet loss caused by congestion and collision in the data transmission process. However, these studies are not directly related to the special structure of the coalmine tunnel and therefore cannot be applied here.…”
Section: Related Studiesmentioning
confidence: 99%
“…Related work: Erman et al (2009) have presented a novel cross-layered communication protocol for efficient data dissemination in multi-sink WSNs. Their protocol combines network wide load balancing, clustering techniques and local routing optimizations with SENSEI architecture which make it efficient on both global and local level.…”
Section: Problem Identification and Proposed Solutionmentioning
confidence: 99%
“…Implementing multiple sinks also reduces latency in the network. [18] introduces P-NLB (Partition-Based Network Load Balanced Routing), a cross-layered pro tocol for data collection in WSN. P-NLB implements multiple sinks in the net work and uses MAC and network layer in routing data.…”
Section: Minimizing Latencymentioning
confidence: 99%
“…Efficient data collection algorithms can result into longer network lifetime. [4,5,9,13,14,17,18] have incorporated this energy-saving approach in their algorithms. They got results th a t show th a t with efficient convergecast schedules, more energy is saved and increseas the network lifetime.…”
Section: Minimizing Energy Consumptionsmentioning
confidence: 99%